Pelvic retroversion is associated with flat back and cam type femoro-acetabular impingement in young elite skiers - Todd, C.; Witwit, W.; Kovac, P.; Swärd, A.; Agnvall, C.; Jonasson, P.; Thoreson, O.; Swärd, L.; Karlsson, J.; Baranto, A. (Journal of Spine, 2016)
The spino-pelvic complex in humans helps to maintain an upright posture, by balancing the spinal sagittal alignment with the hip joints and pelvic girdle. The extent of how the hip joint may influence the spino-pelvic alignment is not fully understood. Hip joint cam femoro-acetabular impingement is a common source of hip and groin disability in young athletes and has been linked to abnormal joint morphology from repetitive loading of the proximal femoral head abutting against the acetabulum. The aim of this study was to compare the radiological parameters of spino-pelvic sagittal alignment and spinal types according to Roussouly`s classification in relation to hip joint cam femoro-acetabular impingement. Methods: The sample group (n=102), mean age (17.7 ± 1.4) years, consisted of elite skiers (n=75) and nonathletes (n=27). Hip joints were examined for increased morphological cam deformity, (alpha angle greater than 55o) with Magnetic Resonance Imaging and standing lateral plain radiographs were taken for measurements of the spinopelvic sagittal alignment. Results: A significant difference was shown in a mixed population (skiers and non-athletes) for an increased Pelvic Tilt angle (13°, SD 10.2) in the presence of morphological hip joint cam deformity compared with participants without cam deformity (8.5°, SD 7.1, P=0.036). Type II Roussouly spines occurred more frequently in skiers in the presence of increased cam (67%) compared with no cam (33%), however, this was not significant (P=0.19). Secondary findings highlighted significant differences shown for the prevalence of cam in a mixed-population for gender; males 60% (n=26) shown to have significantly more cam deformity compared with females 22% (n=10, P=0.001). Similar for height, with taller participants being shown to have significantly more cam deformity >177cm (SD 7.6) compared with no cam deformity <170 cm (SD 7.5, P=0.001). Conclusion: A significant difference was shown with an increased Pelvic Tilt angle for an age-matched mixedgroup of elite skiers and non-athletes in the presence of increased morphological hip joint cam type femoro-acetabular impingement. Moreover, Elite skiers were shown to have an increased distribution of spinal Type II classification according to Roussouly in the presence of an increased frequency of cam femoro-acetabular impingement.